Back Cover: Experimental Realization of Optimal Time‐Reversal on an Atom Chip for Quantum Undo Operations (Adv. Quantum Technol. 12/2022). Issue 12 (12th December 2022) - Mastroserio, Ivana; Gherardini, Stefano; Lovecchio, Cosimo; Calarco, Tommaso; Montangero, Simone; Cataliotti, Francesco S.; Caruso, Filippo
Abstract : In article number 2200057, Filippo Caruso and colleagues experimentally test a method to faithfully time‐invert the dynamical evolution of a very fragile quantum system realized with a Bose‐Einstein condensate of 87Rb within an atom chip device. This task is achieved by applying the quantum optimal control theory to the condensate dynamics by driving it back and forth in time on the five‐fold Hilbert space given by the F=2 rubidium hyperfine ground state, here represented by five atomic clouds of different colors. The cover image represents how optimal control pulses, here depicted in fictitious Cartesian axes given by the hands of the clock, are successfully applied along several paths in the Hilbert space of the quantum system in order to perform different time‐reversed evolutions. In some platforms, like the gate‐based one presented in this paper, the time‐reversal of the last performed operation can be related to the undo command of a quantum computer. Hence, the final results here achieved can be effectively qualified as a proof‐of‐principle of quantum undo operations, whereby the external user can reverse at will the few last calculations executed in a past step of a computational routine. Image created by I. Mastroserio. Background image based on template from PoweredTemplate.